(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: The quality of medical services in general and medical examination and treatment services in particular are always interested and continuously improved by hospitals, especially districts hospitals. Objectives: Describe the satisfaction of patients and their relatives with the quality of medical examination and treatment services at district hospitals. Methods: Cross-sectional survey, quantitative research. Results: This study collected information from 420 patients and their relatives at 6 districts hospital, Thanh Hoa province through questionnaires. The results showed that the quality score and satisfaction rate of patients were quite high, with scores and rates respectively (3.63 - 4.26 points) and (72.6% - 85.2%).